Best Answer

When dealing with a right angled triangle trigonometric functions can be defined by :-

cos x = adjacent/hypotenuse

sin x = opposite/hypotenuse

Therefore cos x/sin x = adj/hyp ÷ opp/hyp = adj/hyp x hyp/opp = adj/opp

The tangent of an angle is given by the formula : opposite/adjacent

The tangent of the complementary angle is therefore : adjacent/opposite

Then cos x/sin x = tan(90-x)

Q: What is the derivative of cosx divided by sinx?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(1-cosx)/sinx + sinx/(1- cosx) = [(1 - cosx)*(1 - cosx) + sinx*sinx]/[sinx*(1-cosx)] = [1 - 2cosx + cos2x + sin2x]/[sinx*(1-cosx)] = [2 - 2cosx]/[sinx*(1-cosx)] = [2*(1-cosx)]/[sinx*(1-cosx)] = 2/sinx = 2cosecx

f(x)=sinx+cosx take the derivative f'(x)=cosx-sinx critical number when x=pi/4

Trig functions have their own special derivatives that you will have to memorize. For instance: the derivative of sinx is cosx. The derivative of cosx is -sinx The derivative of tanx is sec2x The derivative of cscx is -cscxcotx The derivative of secx is secxtanx The derivative of cotx is -csc2x

2

The derivative of 2^x is 2^x * ln2 so the derivative of 2^cosx * ln2 multiplied by d/dx of cox, which is -sinx so the derivative of the inside function is -sinx * 2^cosx *ln2. As to the final question, using the chain rule, d/dx (2^cosx)^0.5 will equal half of (2^cosx)^-0.5 * -sinx * 2^cosx * ln2

Related questions

d/dx(sinx-cosx)=cosx--sinx=cosx+sinx

-sinx

(1-cosx)/sinx + sinx/(1- cosx) = [(1 - cosx)*(1 - cosx) + sinx*sinx]/[sinx*(1-cosx)] = [1 - 2cosx + cos2x + sin2x]/[sinx*(1-cosx)] = [2 - 2cosx]/[sinx*(1-cosx)] = [2*(1-cosx)]/[sinx*(1-cosx)] = 2/sinx = 2cosecx

y=1/sinxy'=(sinx*d/dx(1)-1*d/dx(sinx))/(sin2x)y'=(sinx*0-1(cosx))/(sin2x)y'=(-cosx)/(sin2x)y'=-(cosx/sinx)*(1/sinx)y'=-cotx*cscx

f(x)=sinx+cosx take the derivative f'(x)=cosx-sinx critical number when x=pi/4

Trig functions have their own special derivatives that you will have to memorize. For instance: the derivative of sinx is cosx. The derivative of cosx is -sinx The derivative of tanx is sec2x The derivative of cscx is -cscxcotx The derivative of secx is secxtanx The derivative of cotx is -csc2x

(cosx)^2-(sinx)^2

d/dx(-cosx)=--sinx=sinx

2

The derivative of 2^x is 2^x * ln2 so the derivative of 2^cosx * ln2 multiplied by d/dx of cox, which is -sinx so the derivative of the inside function is -sinx * 2^cosx *ln2. As to the final question, using the chain rule, d/dx (2^cosx)^0.5 will equal half of (2^cosx)^-0.5 * -sinx * 2^cosx * ln2

2

derivative (7cosx) = -ln(7) 7cosx sinx dx